1
$\begingroup$

This is related to the scaling solution of the hydrodynamic equations. I get a relation for the scaling parameter $b$:

$\ddot{b} = -\omega^2(t)*b + \omega_0^2/b^3$

When the trap for the condensate in suddenly switched off $\omega(t)$ goes to zero, so you get the equation

$\ddot{b} = \omega_0^2/b^3$ with initial conditions $b(0)=1$ and $\dot{b}(0) = 0$.

What would be the solution for $b(t)$?

$\endgroup$
1
$\begingroup$

The equation is $$\frac{d^2b}{dt^2} = \frac{\omega_0^2}{\, b^3 \, }$$ Multiply both sides of the equation by $\frac{db}{dt}$ and obtain $$\frac{d^2b}{dt^2} \, \frac{db}{dt} = \frac{\omega_0^2}{\, b^3 \, } \, \frac{db}{dt}$$ which can be interpreted as $$\frac{db}{dt} \, \frac{d}{dt}\left(\frac{db}{dt}\right) = \Big(\omega_0^2\, b^{-3}\Big) \, \frac{db}{dt}$$ which by going backwards with chain rule is the same as $$\frac{1}{2}\, \frac{d}{dt}\left(\frac{db}{dt}\right)^2 = \frac{d}{dt} \Big(\omega_0^2\, \frac{b^{-2}}{-2}\Big)$$ $$\frac{1}{2}\, \frac{d}{dt}\left(\frac{db}{dt}\right)^2 = -\, \frac{1}{2}\frac{d}{dt} \Big(\omega_0^2\, b^{-2}\Big)$$ and after cancelling the one half $$ \frac{d}{dt}\left(\frac{db}{dt}\right)^2 = -\,\frac{d}{dt} \Big(\omega_0^2\, b^{-2}\Big)$$ Integrate both sides with respect to $t$ $$ \left(\frac{db}{dt}\right)^2 = E_0 - \omega_0^2\, b^{-2}$$ $$ \left(\frac{db}{dt}\right)^2 = \frac{E_0 \, b^2 - \omega_0^2}{b^2}$$ $$ b^2 \, \left(\frac{db}{dt}\right)^2 = {E_0 \, b^2 - \omega_0^2}$$ $$ \left(b \, \frac{db}{dt}\right)^2 = {E_0 \, b^2 - \omega_0^2}$$ $$ \left(\frac{1}{2} \, \frac{d(b^2)}{dt}\right)^2 = {E_0 \, b^2 - \omega_0^2}$$ $$ \left(\frac{d(b^2)}{dt}\right)^2 = {4 \, E_0 \, b^2 - 4 \, \omega_0^2}$$ When $\frac{db}{dt}(0) = 0$ and $b(0) = 1$ we arrive at $E_0 = \omega_0^2$. Change the dependent variable by setting $u = b^2$ and the equation becomes $$ \left(\frac{du}{dt}\right)^2 = {4 \, E_0 \, u - 4 \, \omega_0^2}$$ or after taking square root on both sides $$ \frac{du}{dt} = \pm \, \sqrt{\, 4 \, E_0 \, u - 4 \, \omega_0^2 \, }$$ This is a separable equation $$ \frac{du}{ 2\, \sqrt{\, E_0 \, u - \omega_0^2 \, }} = \pm \, dt$$ $$ \frac{d\big(E_0 \, u - \omega_0^2 \big)}{ 2\, \sqrt{\, E_0 \, u - \omega_0^2 \, }} = \pm \, E_0 \, dt$$ $$ d \Big( \sqrt{\, E_0 \, u - \omega_0^2 \, } \Big) = \pm \, E_0 \, dt$$ Integrate both sides $$\sqrt{\, E_0 \, u - \omega_0^2 \, } = C_0 \pm E_0 \, t $$ Square both sides $${\, E_0 \, u - \omega_0^2 \, } = \big(\, C_0 \pm E_0 \, t \,\big)^2 $$ and solve for $u$ $$ u = \frac{1}{E_0} \, \big(\, C_0 \pm E_0 \, t \, \big)^2 + \frac{\omega_0^2}{E_0}$$ Return back to $u = b^2$ $$b^2 = \frac{1}{E_0} \, \big(\, C_0 \pm E_0 \, t \, \big)^2 + \frac{\omega_0^2}{E_0}$$ so finally $$b(t) = \pm \, \sqrt{ \, \frac{1}{E_0} \, \big(\, C_0 \pm E_0 \, t \, \big)^2 + \frac{\omega_0^2}{E_0} \, }$$ However, we know that $E_0 = \omega_0^2$ so $$b(t) = \pm \, \sqrt{ \, \frac{1}{\omega_0^2} \, \big(\, C_0 \pm \omega_0^2 \, t \, \big)^2 + 1 \, }$$ Thus, $b(0) = 1$ is possible when $C_0 = 0$ and finally $$b(t) = \sqrt{ \, \omega_0^2 \, t^2 + 1 \, }$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.